PEMBUATAN ZEOLIT TERMODIFIKASI HEKSADESILTRIMETILAMONIUM (HDTMA) UNTUK APLIKASI PUPUK N SLOW RELEASE - Tidora Juliana Worisio; Dina Kartika Maharani (Unesa Journal of Chemistry, 2023)
This study aims to determine the release of nitrogen levels in fertilizer samples by varying the ratio of zeolite volume to cationic surfactant mass and knowing the chemical characterization of FTIR. In this study natural zeolite and hexadecyltrimethylammonium (HDTMA) were used as the main ingredients. Fertilizer production in this study by activating natural zeolite using 1M HCl then added surfactant HDTMA 0.05M with a ratio of 1: 1, 1: 3, 1: 5, then added a 0.05M NaNO3 solution as a nitrogen source which then tested slow release on land for 7 days. The results of the chemical characterization of FTIR showed a band shift in activated zeolite, HDTMA modified zeolite (1: 1), and ZMS (I). The release of nitrogen levels on day 0 of ZMS (I) was smaller than 0,00059% but on day 7 the nitrogen release was smaller in zeolite activated by 1.3339% compared to ZMS (I) which on day 7 was 1.625% .